Electrodeposition Mechanism of La3+ on Al, Ga and Al-Ga Alloy Cathodes in LiCl-KCl Eutectic Salt. Issue 6 (21st June 2021) - Yang, Da-Wei; Jiang, Shi-Lin; Liu, Ya-Lan; Yin, Tai-Qi; Li, Mei; Wang, Lin; Luo, Wan; Chai, Zhi-Fang; Shi, Wei-Qun
Abstract : Studying the electrodeposition mechanism of La 3+ in LiCl-KCl salt is extremely important for understanding the main characteristics of the deposition of An/Ln in the pyrochemical reprocessing of spent nuclear fuels. In this work, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and Tafel methods were employed to investigate the electrodeposition mechanism and kinetic processes of La 3+ on Al, Ga and Al-Ga alloy cathodes in LiCl-KCl eutectic salt at the temperature range of 723−873 K. The EIS spectra were measured by applying a minimum overpotential near the equilibrium potential, and the suitable equivalent circuits were fitted. The values of exchange current density ( i 0 ) calculated by EIS ranged from 0.078 to 0.42 A cm −2 . Finally, Al2 Ga2 La ternary and Al3 La, Ga6 La binary alloys were obtained by the potentiostatic electrolysis, which were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS).